An improved spreadsheet for calculating limb length discrepancy and epiphysiodesis timing using the multiplier method. (August 2016) - Mills, Gavin; Nelson, Scott
Purpose: The multiplier method is a technique to predict limb length discrepancy (LLD) at maturity in pediatric patients. Various tools have been developed for performing the multiplier calculations to predict LLD and timing of epiphysiodesis. These include multiplier/growth applications (apps) and a spreadsheet which have helped to facilitate LLC calculations in an efficient and easy manner. We have updated the spreadsheet to improve features for making LLD calculations and facilitate pasting data into electronic medical records (EMRs). Methods: Tools currently in use were critically examined for features that limited their function, created possible sources of error or could be more user-friendly. These features were modified and recreated in an improved Excel spreadsheet that uses patient age, sex, limb lengths, and previous lengthening surgeries as inputs to predict LLD at maturity and offer options for timing of epiphysiodesis for both congenital and developmental LLD. Our multiplier spreadsheet function was then compared to manual calculations and other multiplier tools for accuracy and ease of use. Results: Our spreadsheet accurately calculates LLD at maturity and timing of epiphysiodesis when compared to other methods. It contains a function to calculate predicted leg lengths after previous lengthenings, and concise single-page worksheets for developmental LLD, congenital LLD, and height prediction. Conclusions: This spreadsheet was developed to provide a more efficient and user-friendly method of calculating LLD at maturity and timing of epiphysiodesis. It can easily be pasted into the EMR for ease of documentation. We recommend this method for both clinical practice and educational use.